Modelling the coefficient of thermal expansion in Ni-based superalloys and bond coatings - Karunaratne, M.S.A.; Kyaw, Si Thu; Jones, Arthur; Morrell, Roger; Thomson, Rachel C. (Springer, 2016)
The coefficient of thermal expansion (CTE) of nickel-based superalloys and bond coat layers was modelled by considering contributions from their constituent phases. The equilibrium phase composition of the examined materials was determined using thermodynamic equilibrium software with an appropriate database for Nibased alloys, whereas the CTE and elastic properties of the principal phases were modelled using published data. The CTEs of individual phases were combined using a number of approaches to determine the CTE of the phase aggregate. As part of this work, the expansion coefficients of the superalloy IN-738LC and bond coat Amdry-995 were measured as a function of temperature and compared with the model predictions. The predicted values were also validated with the published data for the single-crystal superalloy CMSX-4 and a number of other Ni-based alloy compositions at 1000 K. A very good agreement between experiment and model output was found, especially up to 800 C. The modelling approaches discussed in this paper have the potential to be an extremely useful tool for the industry and for the designers of new coating systems.